Investigation of the possibility of using waste cooking oil as a rejuvenating agent for aged bitumen - Zargar, M.; Ahmadinia, E.; Asli, H.; Karim, M.R. (2012)
The ageing of the bitumen during storage, mixing, transport and laying on the road, as well as in service life, are the most important problems presented by the use of bitumen in pavements. This paper investigates the possibility of using waste cooking oil (WCO), which is a waste material that pollutes landfills and rivers, as an alternative natural rejuvenating agent for aged bitumen to a condition that resembles the original bitumen. With this target, the physical and chemical properties of the original bitumen, aged bitumen and rejuvenated bitumen were measured and compared by the bitumen binder tests - softening point, penetration, Brookfield viscosity, dynamic shear rheometer and Fourier transform infrared spectroscopy. In addition, the behaviour of the WCO rejuvenated bitumen is investigated and compared with virgin bitumen after using the rolling thin film oven ageing process. In general, the results showed that using 3-4 of WCO the aged bitumen group 40/50 was rejuvenated to a condition that closely resembled the physical, rheological properties of the original bitumen (80/100), however, there was a difference in the tendency to ageing between the WCO rejuvenated bitumen and the virgin bitumen during mixing, transport and laying on the road.